Merging Ultrasound Images Based on Up and Down Motion Blur Technique - Hussein, Esraa Saad; Razak, Muslim Ali; Hussein, Tabarak Jaber; Abbas-Mahmoud, Mustafa Mohamed (American Journal of Botany and Bioengineering, 2025)
Merging digital images is an essential step in digital image processing, as it allows information from two or more images to be combined into one image to obtain a highquality and clear image. This work simulates the case of motion blur with a different block size of 11,9, 7,5,3 pixels. The point spread function is programmed to obtain a linear blur motion. I used to simulate motion blur for half of the image in two parts (the top half and the bottom half). We relied on the traditional methods used to combine distorted grayscale images, such as addition and multiplication, and the proposed new techniques depend on weights, which are the standard deviation. The added, distorted, and common edges of the original image, the upper blurry half, the lower blurry half, and the merged image were detected. Different thresholds are used to compare edges visually and by identifying added, deleted and common edges, we can determine the best fusion method.